Radio observations of supernova remnants and the surrounding molecular gas - Dubner, Gloria Mabel (2011)
Supernova Remnants (SNRs) are believed to be the main source of Galactic cosmic rays (CR). The strong SNR shocks provide ideal acceleration sites for particles of at least ∼ 1014 eV/nucleon. Radio continuum studies of SNRs carried out with good sensitivity and high angular resolution convey information about three main aspects of the SNRs: morphology, polarization and spectrum. Based on this information it is possible to localize sites of higher compression and particle acceleration as well as the orientation and degree of order of the magnetic fields, and in some cases even its intensity. All this information, when complemented with the study of the distribution and kinematics of the surrounding interstellar gas, results in a very useful dataset to investigate the role of SNRs as cosmic ray accelerators. In this presentation, I analyze the radio observations of SNRs and surrounding molecular clouds, showing the contribution of these studies to the understanding of the role of SNRs as factories of CRs.